Pengaruh Lingkungan Kerja Fisik dan Kepuasan Kerja terhadap Motivasi Kerja Guru di MTs Nurul Iman Sindangkerta Kabupaten Bandung Barat - Salma Fitrya Az-zahra; Juddy Prabowo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Education plays an important role in improving the quality of human resources. Advances in education occur every year. One of the official educational institutions prioritizing the development of student potential is Mts Nurul Iman Sindangkerta in West Bandung Regency. The aim of the research is to determine the partial and simultaneous effects of the physical work environment and job satisfaction on teacher work motivation. The method used is a quantitative method with a multiple linear regression analysis approach and the coefficient of determination using SPSS 25. Data was collected through the distribution of questionnaires to 33 teachers as respondents. The research results show that the physical work environment has a positive effect on teacher work motivation. Simultaneously, the physical work environment and job satisfaction significantly influence teacher work motivation. This means that with a good physical work environment and a high level of job satisfaction among teachers, the motivation of the teachers will also increase.